(untitled) - bin Mohamad Fozi , Muhammad Faidhi Afiq (Universiti Teknologi PETRONAS, 2014)

(untitled)
Low resistivity and low contrast zone have been identified in clastic rock bodies and one of the reasons for this behavior is due to bioturbated sand. The resistivity of this zone is similar to the resistivity of formation water bearing zone. To understand this unique behavior, study is focused on investigation of clastic rock bodies which includes the bypass zone otherwise known as bioturbated sand. Features of clastis deposits were studied while understanding environment of bioturbated sand is also undertaken. The main objective of the research is to evaluate the LRLC zone with accompanied objective including investigating clastic sediment from selected Seri Iskandar outcrop and doing fieldwork in Pantai Seri Tujuh to enhance the understanding of modern environment of bioturbated sand.